Penerapan Metode MOORA dan Pengambilan Keputusan untuk Penentuan Karyawan Terbaik - Nova Nika Silaban (ADA Research Center, 2024)
Employees are one of the most important assets owned by a company in its efforts to maintain survival, development, the ability to compete and earn profits. Selection of the best employees will produce valid and useful information for employee administrative decisions such as promotions, training, transfers including reward systems and other decisions. The Decision Support System is a computerized system and is designed to increase effectiveness in decision making to solve semi-structured and unstructured problems so that the decision-making process carried out can be of higher quality. This application that will be created is an application that is guided by the MOORA method. In this study, the ranking results were obtained as follows: Lidya (A2) received the highest preference value of 0.533, placing her in the first rank. Meanwhile, Andre (A1) is in the second rank with a preference value of 0.458. Followed by Naomi (A4) with a value of 0.429, Muhammad (A5) with a value of 0.394, and Friska (A3) with a value of 0.337, occupying the fifth rank.